Performance analysis on the thermosiphon beam air conditioning and mechanical ventilation system - Chia, Marcus Wen Jun (Nanyang Technological University, 2022)
Air Conditioning and Mechanical Ventilation (ACMV) systems have been around for many years to provide cooling to many buildings around the world. However, due to the alarming rates of global warming, it is essential to develop new innovative ACMV technology to reduce the carbon emissions due to the electrical consumption of the ACMVs.